Practical Aspects of Clinical Manifestations, Pathogenesis and Therapy of Alcoholic Liver Disease and Non-alcoholic Fatty Liver Disease: Expert Opinion - V. V. Tsukanov; M. F. Osipenko; E. V. Beloborodova; M. A. Livzan; I. B. Khlynov; S. A. Alekseenko; Yu. P. Sivolap; J. L. Tonkikh; A. V. Vasyutin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present the results of an expert discussion of modern aspects of the clinical manifestations, pathogenesis and treatment of alcoholic liver disease (ALD) and non-alcoholic fatty liver disease (NAFLD).Key points. ALD and NAFLD are characterized by high prevalence and have a significant impact on public health. For the diagnosis of liver pathology, it is important to determine the stage of fibrosis and the severity of the exacerbation of the disease. In the treatment of ALD, it is recommended to achieve abstinence, proper nutrition, the appointment of B vitamins, drugs with cytoprotective activity. In severe hepatitis, corticosteroids may be prescribed. In the treatment of NAFLD, diet and lifestyle modification, weight loss, the use of insulin sensitizers, vitamin E, statins (in the presence of hyperlipidemia) and drugs with metabolic activity are effective.Currently, a point of view is being actively expressed about the synergism of the action of alcohol and the metabolic syndrome on the development of fibrosis, cirrhosis, and hepatocellular carcinoma. The current international consensus recommends a change in the nomenclature of NAFLD and ALD and proposes the terms “metabolically associated steatotic liver disease” and “metabolically associated alcoholic liver disease”.Conclusion. The closeness of the clinical manifestations and pathogenesis of NAFLD and ALD justifies attention to drugs with metabolic activity, which are recommended by the Russian Gastroenterological Association and Russian Scientific Liver Society for the treatment of these diseases. The experts support the suggestion to quantify alcohol consumption in patients with NAFLD in order to change the management of patients, if necessary.